Fasting blood glucose mediated the association between a body shape index and depression: a cross sectional study from NHANES 2017–2023 - Chen, Yang-Tao; Wei, Can-Jie; Wang, Zhao-Chu; Xie, Ya-Meng; Wang, Xun; Wang, Jing (Frontiers in Nutrition, 2025)
ObjectiveThe objective was to evaluate ABSI’s association with depression and explore FBG as a possible mediating factor.MethodsData from 8,748 NHANES participants (2017–2023) were analyzed. Logistic regression analyses assessed ABSI-depression associations, while mediation models tested FBG’s intermediary role. We conducted stratified analyses and interaction test to assess the impact of gender, age, race, PIR, education, alcohol use, current smoking status, BMI, hypertension history and hypercholesterolemia history on the study outcomes.ResultsThe fully adjusted logistic regression models demonstrated a significant positive association between ABSI and depression (OR = 1.20, 95%CI: 1.00, 1.44, p = 0.0497). Stratified analyses and interaction test showed that this association was significant only among participants with some college education or above (P for interaction < 0.05). No significant interactions were found across other subgroups. Mediation analyses revealed that FBG partially mediated the relationship between ABSI and depression (15.8%, p < 0.0001).ConclusionABSI was associated with depression, potentially mediated through FBG.